Paths to a world-class university lessons from practices and experiences (Global perspectives on higher education, 2011)
Within higher education, world-class universities are regarded as elite research universities and play a critical role in developing human resources and generating new knowledge in the context of a knowledge-based economy. Governments around the world have made the operation of their universities at the cutting edge of intellectual and scientific development their policy priority; and top universities make every effort to compete at this global stage. ?Paths to A World-Class University? provides insights into recent and ongoing experiences of building world-class universities, both at a national level and at an institutional level. It collects fifteen essays, most of which originated from papers presented at ?The Third International Conference on World-Class Universities?, held in November 2009 in Shanghai, China, and organized by the Center for World-Class Universities of Shanghai Jiao Tong University. Divided into two parts, the book: - focuses on the role of world-class universities in national systems; and - looks at institutional experiences and lessons in building world-class universities. This book not only represents a contribution to the ongoing discussion on the topic of building world-class universities, but can be seen a continuation of the previous two volumes on this topic - ?World-Class Universities and Ranking: Aiming beyond Status? and ?The World-Class University as Part of a New Higher Education Paradigm: From Institutional Qualities to Systemic Excellence?. All three books will be useful reading for students and academics in higher education generally, in addition to policy makers and informed practitioners.